(untitled) (Costos y Gestión, 2020)
Distance learning provides opportunities for individuals who can combine their education with their work. It also enables institutions to respond to a larger number of students and offer both hybrid courses and full distance options. The use of Internet in education has given rise to e-learning. Given the expected benefits it is necessary to identify and document the necessary resources for its development. The information on the costs derived from e-learning projects development and supported by rigorous analysis is scarce. This work provides a description of the required institutional resources for the development and delivery of courses based on e-learning and a cost analysis. The methodology for determining the cost factors is based on a literature review, and on experts’ interviews. The cost analysis is based on the General Cost Theory. As a result, it arises that labor costs has the greatest impact on the final result. It is expected that the detailed description of cost analysis would be useful for future assessments of this mode of education and constitute a support tool for decision making in the field of high education.